Association between maternal education and survival after childhood cancer. Issue 5 (24th January 2019) - Isaevska, Elena; Popovic, Maja; Alessi, Daniela; Mosso, Maria Luisa; Sacerdote, Carlotta; Magnani, Corrado; Pastore, Guido; Rosso, Tiziana; Zengarini, Nicolás; Dockerty, John; Merletti, Franco; Maule, Milena
Abstract: Background: Several nonbiological factors, including socioeconomic status indicators and other family characteristics, influence survival from childhood cancers. Our study explores the association between parental education and childhood cancer survival. Methods: The specialized Childhood Cancer Registry of the Piedmont region in Italy provided data on all the cases (aged 0–14) diagnosed with cancer in the period 1976–2011 who resided in the city of Turin (capital of the Piedmont region) at least once since 1971. Information on parental education was extracted from the Turin Longitudinal Study by record linkage. The association between parental educational level and survival was estimated using Cox regression. Results: The study included 949 children. We observed a disadvantage in the overall survival for children of less educated mothers. No such effect was observed for paternal education. The effect of maternal education was particularly strong for central nervous system tumors (hazard ratios, 2.9; 95% confidence interval, 1.1–8.0). A similar effect, though smaller in magnitude, was observed for leukemia and embryonal tumors, whereas the estimates for lymphoma were imprecise. Conclusions: Our study shows an association between maternal educational level and survival in children with central nervous system tumors, a diagnosis that often requires long‐lasting treatment and special care. Giving support to the families of affected children to provide them the optimal care has the potential to improve children's cancer treatment outcomes.